Effect of 12-month intervention with lipid-based nutrient supplement on the physical activity of Malawian toddlers: a randomised, controlled trial - A. Pulakka; Y. B. Cheung; K. Maleta; K. G. Dewey; C. Kumwenda; J. Bendabenda; U. Ashorn; P. Ashorn (Cambridge University Press, 2025)
Physical activity is beneficial for children’s well-being. The effect of dietary supplementation on children’s physical activity in food-insecure areas remains little studied. We examined the effects of a lipid-based nutrient supplement (LNS) on children’s objectively measured physical activity in a randomised, controlled, outcome-assessor-blinded trial. Mothers of the children received one capsule daily of Fe-folic acid (IFA),
one capsule containing eighteen micronutrients (MMN) or one 20 g sachet of LNS (containing twenty-two MMN, protein, carbohydrates, essential fatty acids and 494 kJ (118 kcal)) during pregnancy and for 6 months thereafter. Children in the IFA and MMN groups received no supplementation, and these groups were collapsed into a single control group; children in the LNS group received 20 g LNS from 6 to
18 months. We measured physical activity with accelerometers over 1 week at 18 months. The main outcome was mean vector magnitude counts/15 s. Of the 728 children at the beginning of child intervention at 6 months, 570 (78 %) provided sufficient data for analysis. The mean accelerometer counts for the 190 children in the LNS group and for the 380 children in the control group were 303 (SD 59) and 301 (SD 56), respectively (Pfor difference =0·65). LNS, given to mothers during pregnancy and 6 months postpartum and to their infants from 6 to 18 months of age, did not increase physical activity among 18-month-old children.